Male and female reproductive morphology in the inseminating genus Astroblepus (Ostariophysi: Siluriformes: Astroblepidae) - Spadella, Maria Angelica; Oliveira, Claudio [UNESP]; Ortega, Hernan; Quagio-Grassiotto, Irani [UNESP]; Burns, John R. (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
The structure of the reproductive organs of males and females of four species of Astroblepus were studied by light microscopy and TEM. In females, the gonadal and urinary orifices are separated. The urinary pore opens at the tip of a urinary papilla. In males, the testes conform to the anastomosing tubular type. Spermatogenesis is partially cystic, with most spermatid stages taking place within the lumen of the seminiferous tubules. The sperm ducts pass through seminal vesicles. The main sperm ducts fuse and join the urinary duct to form a urogenital duct that passes through to the tip of an long urogenital papilla. A circularly arranged skeletal muscle at the base of the urogenital papilla probably serves as a sphincter. The spermatozoon is an anacrosomal introsperm with an elongate, conical nucleus and an elongate midpiece. The midpiece contains numerous fused mitochondria that form rings within the cytoplasmic collar, but no vesicles were observed. The flagellum has a classic 9 + 2 axoneme with the A-tubules of the peripheral doublets being electron-dense. Two lateral fins on the posterior part of the flagellum have electron-dense termini. Nuclear chromatin is highly condensed, and the two centrioles are oriented perpendicularly to one another and are contained within a nuclear fossa. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Intromittent organ; Sperm ultrastructure; Introsperm; Insemination; Partially cystic spermatogenesis